2007
DOI: 10.1152/ajpendo.00034.2007
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous adipose tissue exerts proinflammatory cytokines after minimal trauma in humans

Abstract: Inflammatory cytokines released from adipose tissue play an important role in different pathological processes. In the present study, we investigated the inflammatory cytokine response of human subcutaneous adipose tissue (SAT) by applying the open-flow microperfusion technique. Four standard 18-gauge microperfusion catheters were inserted into periumbilical SAT of eight healthy male volunteers [29 Ϯ 3 yr, BMI 24.3 Ϯ 1.9 (mean Ϯ SD)]. SAT probe effluents were collected at 60-min intervals for 8 h after cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
(40 reference statements)
3
35
0
1
Order By: Relevance
“…The release of inflammatory cytokines from subcutaneous adipose tissue even after minimal trauma, as also proved in our case by the positivity of TNF-(1 staining, mainly in, the infiltrated inflammatory cells in damaged tissues, may play a role in the inflammatory response (24). Also, the positivity for TNF-(1 correlated with an intense signal immunolocalization for I-CAM1, in accordance with previous studies, showing that TNF-(1 induces the upregulation of ICAM-l (25,26).…”
Section: Immunohistochemical Analysis Positive Staining Was Observsupporting
confidence: 81%
See 2 more Smart Citations
“…The release of inflammatory cytokines from subcutaneous adipose tissue even after minimal trauma, as also proved in our case by the positivity of TNF-(1 staining, mainly in, the infiltrated inflammatory cells in damaged tissues, may play a role in the inflammatory response (24). Also, the positivity for TNF-(1 correlated with an intense signal immunolocalization for I-CAM1, in accordance with previous studies, showing that TNF-(1 induces the upregulation of ICAM-l (25,26).…”
Section: Immunohistochemical Analysis Positive Staining Was Observsupporting
confidence: 81%
“…Moreover,authorsunderlinetherole ofintradermal injection as possible trigger of the adverse immune reaction, suggesting deep cutaneous penetration of the drug to avoid these reactions; in fact, the use of adequate training and/or automated injection devices has .been associated with an estimated 60% rate of reduction in the incidence of adverse cutaneous side effects (12,17,24,28).…”
Section: Immunohistochemical Analysis Positive Staining Was Observmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight loss induced by very low-caloric diet reduces IL-6 levels and improves insulin sensitivity in obese subjects (39) . IL-6 concentrations in subcutaneous adipose tissue are increased by local insulin infusion (40) . At cellular level, IL-6 has demonstrated that it exerts inhibitory effects on gene transcription of IRS-1, GLUT-4, and peroxisome proliferator-activated receptor gamma (PPAR-gamma).…”
Section: Adipokines Insulin Resistance and Type 2 Diabetesmentioning
confidence: 99%
“…TNF-α and IL-6 are both secreted by adipocytes, although only IL-6 seems to be released from adipose tissue to the systemic circulation (44) . The concentrations of TNF-α, IL-6, IL-1beta and IL-8 in adipose tissue seem to be unrelated to their systemic concentrations, acting more likely as paracrine mediators (40,44) . Adiponectin is a protein secreted by adipocytes which retains significant homology with collagen X and VII, as well as with the complement factor C1q (45) .…”
Section: Adipokines Insulin Resistance and Type 2 Diabetesmentioning
confidence: 99%